Strategi Key Opinion Leader (KOL) Untuk Meningkatkan Keputusan Pembelian Konsumen Terhadap Produk Wardah - Erwin Permana; Anita Wulandari; Rizky Alfiani Fadilah; Syamsurizal, Syamsurizal (Lembaga Pengembangan Kinerja Dosen, 2024)
Utilization of Key Opinion Leaders (KOL) is one of the digital marketing strategies that is widely used today. KOL is not only used by new business people, even established business people with popular brands also use KOL. One of them is Wardah cosmetics. This research aims to analyze the Key Opinion Leader (KOL) strategy to improve consumer purchasing decisions for Wardah products. The research was conducted using a descriptive qualitative approach. Research data comes from the results of reviews of official publications and searches on various official databases and popular digital sites. The research results show that Wardah did several things in its KOL utilization strategy, namely: 1). Wardah chooses Key Opinion Leaders (KOL) who have a positive image and are relevant to the target market and collaborate with beauty influencers, fashion influencers and lifestyle influencers to promote their products. 2). Wardah collaborates with Key Opinion Leaders (KOL) to create interesting and informative content about Wardah products, the content will be creative and original. 3). Wardah measures the effectiveness of the Key Opinion Leader (KOL) strategy by tracking metrics such as reach, engagement and conversion using social media analytics tools to track the performance obtained. Wardah's success in using Key Opinion Leaders (KOL) was proven when it carried out a C-Defense Series product campaign which showed significant results with increased views and engagement, this helped Wardah reach consumers and increase sales effectively